Rhetorical and Figurative Phenomena in the Prose and Poetry of Ibn Abi Ḥajlah: Selected Examples from Diwan al-Ṣababah - Bin Misra , Nawal Ben; Al-Heib, Israa Ahmed Fawzi (Arts for Linguistic & Literary Studies, 2025)
This study investigates the rhetorical and figurative dimensions in the prose and poetry of Ibn Abi Ḥajlah, with special reference to selected passages from his renowned book Diwan al-Ṣababah, a classical work on love and longing. Structured into an introduction, a preface, and two sections, the research first contextualizes the author and his text while clarifying central rhetorical concepts such as ʿIlm al-Badīʿ and ʿIlm al-Bayan. The first section highlights Ibn Aiī Ḥajlah’s prose style, which is marked by various rhetorical embellishments, most notably rhymed prose (sajʿ), antithesis (ṭibaq), Quranic allusion (iqtibas), and literary incorporation (taḍmin). The second section examines his poetic expressions, where figurative devices such as simile and metaphor emerge as prominent stylistic features. Through this dual focus, the study concludes that Ibn Abi Ḥajlah’s literary production—both in prose and verse—reveals an impressive command of rhetorical and figurative techniques that reflect his creative eloquence, refined style, and careful artistic selection. These findings underscore the significance of his contributions to Arabic rhetorical tradition and highlight the aesthetic richness of Diwan al-Ṣababah as a literary and cultural artifact.